A new species of Thomasomys Coues, 1884 (Rodentia: Sigmodontinae) from the montane forests of northern Peru with comments on the “aureus” group - Ruelas, Dennisse (2021)
We describe a new species of the cricetid rodent Thomasomys (Sigmodontinae) of the "aureus" group based on four specimens collected from Carmen de la Frontera, Piura Department, Peru. This new species has a very long and white tail, very long mystacial vibrissae that extend posteriorly beyond the pinnae, and a distinctive cranial and dental morphology that differ from any other known species of Thomasomys. It is also one of the largest species of Thomasomys, exceeded in size only by T. apeco. A phylogenetic analysis using sequences of Cytb recovered this species within a non-monophyletic "aureus" group with a genetic distance between 5.47% (with T. auricularis) to 10.17% (with Thomasomys sp. 1). In addition to this finding, the phylogenetic position of T. apeco, T. praetor, and T. pyrrhonotus are presented for the first time, prompting a discussion on the nature of the "aureus" group.